Public Awareness Towards Telehealth Services - SHREE, MS. K.C. RAJA; MS. ASWANI J, (The journal of contemporary issues in business and government, 2020)
The study is to identify the variables such as digitalization, convenience and privacy categories which includes the factors like telecommunication, smart watch, medical devices, social media, health apps, cost reduction, long travels, waiting time, potential adopters, specialist care, data privacy, security, doctor-patient interaction, confidentiality, patient’s doubt clearance and electronic medical record, all together showing to what level it influences people to approach telehealth. Telehealth innovations influence the people with their services where technology has the potential to increase the quality of healthcare and make it available to more people. Telehealth provides opportunities for health care to become more efficient, better organised and closer to home. The study finds out people's understanding on Telehealth services and measures the relationship among various factors that influence Telehealth practices among people. The conclusion of the study states about various factors that influence people to prefer Telehealth, such as digitalization, convenience factors and privacy factors, where it all has a positive linear relationship towards telehealth approach.